Molecular docking, dynamics simulations and 3D-QSAR modeling of arylpiperazine derivatives of 3, 5-dioxo-(2H, 4H)-1, 2, 4-triazine as 5-HT1AR agonists. (February 2019) - Sherin, D.R.; Geethu, C.K.; Prabhakaran, Jaya; Mann, J. John; Dileep Kumar, J.S.; Manojkumar, T.K.
Graphical abstract: Highlights: Homology model of 5HT1A R. In Silico validation of derivatives of 3, 5-dioxo-(2H, 4H)-1, 2, 4-triazine as 5HT1A R ligands. Docking and dynamics simulations of 5HT1A R ligands. 3D-QSAR model of 5HT1A R ligands. Abstract: Serotonin receptor, 5-HT1A R, agonists and partial agonists have established drug candidates for psychiatric and neurologic disorders. Recently, we reported the synthesis and evaluation of arylpiperazine derivatives of 3, 5-dioxo-(2H, 4H)-1, 2, 4-triazine as 5-HT1A R ligands. Herein, we generated a homology model of the receptor and docked the ligands against it, predicted the stability of the receptor model and complexes by molecular dynamics and generated a 3D-QSAR model for the arylpiperazine derivatives of 3, 5-dioxo-(2H, 4H)-1, 2, 4-triazine. The model suggests the hydrophobic part that arises from the aromatic region and the electron withdrawing parts play a vital role in the agonist activity of the lead molecules.